2015
DOI: 10.1093/neuonc/nov117
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter imaging outcomes study of The Cancer Genome Atlas glioblastoma patient cohort: imaging predictors of overall and progression-free survival

Abstract: Preoperative MRI parameters have a significant prognostic role in predicting survival in patients with GBM, thus making them useful for patient stratification and endpoint biomarkers in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 38 publications
1
65
3
3
Order By: Relevance
“…MR images of TCGA cohort have been obtained from The Cancer Imaging Archive (TCIA) website 17,34,35 . We excluded cases with any evidence of prior neurosurgical intervention except biopsy, lack of treatment history, or loss of T1CE or FLAIR/T2 images.…”
Section: Methodsmentioning
confidence: 99%
“…MR images of TCGA cohort have been obtained from The Cancer Imaging Archive (TCIA) website 17,34,35 . We excluded cases with any evidence of prior neurosurgical intervention except biopsy, lack of treatment history, or loss of T1CE or FLAIR/T2 images.…”
Section: Methodsmentioning
confidence: 99%
“…The MRI scans were interpreted by two neuroradiologists blinded to the patient outcome. We selected eight cardinal tumor‐related imaging features and dichotomized these features according to previous guidelines using the following criteria: ADC value,12, 13 peritumoral edema,14 contrast‐enhancing tumor (CET),15 necrosis,16 formation of cysts (cyst),16 noncontrast‐enhancing tumor (nCET),17 T1/Flair ratio,16 and deep white matter invasion 15. The exact dichotomy information is listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This differs from the work presented in this study whereby quantitative rather than categorical volumetric assessment was performed, by a single radiologist using a technique, which has previously shown good intra and inter-observer variability [14], and the surrounding T2 signal abnormality/oedema was not included in the whole tumour volume. A larger quantitative volumetric analysis of 94 GBM by the same group also reported increased proportional enhancement was associated with increased mortality (p=0.003), but as with the previously study included the perilesional T2 and FLAIR signal abnormality as part of the whole tumour volume [30]. PerezBeteta et al assessed the pre-treatment geometry in 117 patients with GBM and reported both increases in tumour volume and contrast enhancing volume were associated with reduced overall survival (p=0.034, hazards ratio 1.574 and p=0.017, hazards ratio 1.659), but no assessment of the proportional enhancement of the tumour was made in this study [31].…”
Section: Parametermentioning
confidence: 63%